(untitled) (Jurnal EurekaMatika, 2018)
Mecimapro is one of company that works in field service. In the tight competition with other companies, Mecimapro tried to increase their service quality. One of the effort to increase the quality is analyzing the factors that need to be more attention and improve to obtain the right and quick solution according to customer’s needs or desires. 5 main dimensions of SERVQUAL Method (Service Quality) is use as a reference to make variables to analyzing service quality. Data analysis that use to analyze the service quality is analysis factor. In this research, parameter estimation method used in factor analysis is Principal Component Factoring (PCF) and Principal Axis Factoring (PAF). The comparison from both of the method will be used to determine the most effective method to analyze the service quality towards costumer satisfaction of K-Pop Concert Organizer Mecimapro. Based on the result of R programming, PCF method is appropriate to use because give a larger proportion of cumulative variance than the PAF method. The factors that need more attention and improved to to increase the quality. The results that obtained from factor analysis is factor of service, facility, communication and readiness. These four factors need to be more attention and improve to increase the service quality of K-Pop Concert Organizer Mecimapro’s customer satisfaction. ABSTRAK Mecimapro merupakan salah satu perusahaan yang bergerak di bidang jasa. Dalam persaingan bisnis yang semakin ketat, Mecimapro berusaha untuk selalu meningkatkan kualitas jasanya. Salah satu usaha yang dilakukan untuk meningkatkan jasanya yaitu dengan menganalisis faktor kualitas jasa apa saja yang perlu lebih diperhatikan dan ditingkatkan agar dapat memberikan solusi yang tepat dan cepat sesuai kebutuhan atau keinginan pelanggan. 5 dimensi pokok SERVQUAL (Service Quality) digunakan sebagai acuan membuat variabel dalam menganalisis kualitas jasa. Analisis data yang digunakan untuk menganalisis kualitas jasa adalah analisis faktor. Pada penelitian ini metode estimasi parameter yang digunakan pada analisis faktor adalah Principal Component Factoring (PCF) dan Principal Axis Factoring (PAF). Kedua metode ini dibandingkan untuk mengetahui metode yang lebih tepat dalam menganalisis kualitas jasa terhadap kepuasan pelanggan K-Pop Concert Organizer Mecimapro. Berdasarkan hasil program R penggunaan metode PCF lebih tepat digunakan karena memberikan proporsi variansi kumulatif yang lebih besar daripada metode PAF. Hasil yang diperoleh dari analisis faktor adalah faktor pelayanan, faktor fasilitas, faktor komunikasi dan faktor kesiapan. Keempat faktor ini yang perlu lebih diperhatikan dan ditingkatkan dalam meningkatkan kualitas jasa terhadap kepuasan pelanggan K-Pop Concert Organizer Mecimapro.